Wrist acupressure for post-operative nausea and vomiting (WrAP): A pilot study. Issue 3 (June 2015) - Cooke, Marie; Rapchuk, Ivan; Doi, Suhail A.; Spooner, Amy; Wendt, Tameka; Best, Jessica; Edwards, Melannie; O'Connell, Leanda; McCabe, Donna; McDonald, John; Fraser, John; Rickard, Claire
Highlights Pilot study found preliminary support for use of acupressure for post-operative nausea/vomiting. Large clinical trial to test efficacy of acupressure for post-operative nausea/vomiting is needed. A cost-effectiveness assessment should be included in a larger clinical trial.